Kafedre fiziologii Sankt Peterburgskoi gosudarsvennoi akademii fizicheskoi kul'tury im. Lesgafta - 80 let - Ageevets, V. U.; Solodkov, A. S. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
About the development and achievements of the St.-Petersburg State P.F.Lesgaft Academy of Physical Culture in it's 80 years of existence.